Ultrastructural evaluation of recovery of injured sciatic nerve at autografting of it’s large defects in rats: Experimental study - Strafun, Sergiy; Gayovich, Vasyl; Savosko, Sergiy (Ukrainian Neurosurgical Journal, 2014)
Introduction. The purpose of the experimental study was ultrastructural and morphometric evaluation of reconstruction efficacy at nerve’s large defects, comparison of efficacy of combined autografting and stimulation for sciatic nerve recovery. Materials and methods. For sciatic nerve’s recovery evaluation we studied it’s distal segment using electron microscopy. Results. Autografting allows to reconstruct large defects of sciatic nerve but it is characterized by low regeneration efficacy and glial and connective scars forming in areas of neurorrhaphy. After 30 days only 47% nerve fibers regenerated. Platelet rich plasma (PRP), NGF and thyroxine stimulate nerve fibers regeneration in distal segment of the nerve. Efficacy of regeneration at PRP using was 85%, thyroxine — 66%, NGF — 65%. Conclusions. Autografting is the «gold standard» for reconstruction of old and large defects of peripheral nerve’s. NGF, thyroxine and PRP stimulate recovery processes after reconstruction: NGF activates myelin fibers regeneration, thyroxine — stimulates myelination, PRP — activates regeneration of unmyelinated nerve fibers and axon – glial interaction.